What if it Were Otherwise? Teachers Use Exams from the Past to Imagine Possible Futures in the Teaching of Literature. Issue 1 (27th November 2022) - Levine, Sarah; Moore, Daniel P.; Bene, Emma; Smith, Michael W.
ABSTRACT: In the United States, standardized tests shape what, how, and why English Language Arts teachers teach. For the last generation, these tests have increasingly taken a narrowly text‐centered approach to literature, making it difficult to enact or research alternatives. But what if it were otherwise? In the current study, we asked teachers to imagine alternatives to the current world of standardized testing. Drawing from a hundred years of New York state exams, we selected reader‐ and text‐centered essay prompts that represented a range of alternatives to current standardized exams. Then we interviewed 30 high school English Language Arts teachers from across the U.S., asking them to imagine what, how, and why they might teach with these alternative prompts in mind. Compared to their responses to a current Common Core aligned exam, when teachers responded to the alternative prompts, they were more likely to imagine selecting texts by authors of color, plan a wide variety of discussion‐based and writing activities, highlight the ethical dimensions of the teaching of literature, and envision the pleasure of aligning their beliefs with their instructional choices. As testing becomes more uniform, studies that imagine alternatives to the status quo allow for a broad exploration of the possibilities of language arts curriculum and instruction, as well as an understanding of teachers' untapped creativity and skill. Abstract : In the United States, standardized tests shape what, how, and why English Language Arts teachers teach. For the last generation, these tests have increasingly taken a narrowly text‐centered approach to literature, making it difficult to enact or research alternatives. But what if it were otherwise? In the current study, we asked teachers to imagine alternatives to the current world of standardized testing.